PERSPEKTIF PEMIKIRAN EMPAT MADZHAB TERKAIT PEMBUNUHAN SEBAGAI PENGHALANG MENDAPATKAN HARTA WARISAN - Sumper Mulia Harahap (IAIN Padangsidimpuan, 2022)
The division of inheritance in Islamic teachings is regulated very clearly and in detail. Each heir has rights and shares them with his parents or relatives who have died. This section is regulated in the Qur'an and Sunnah with clear explanations and mention of numbers. However, an heir may lose his inheritance rights in certain cases. One way is to kill the heir. This article will describe and analyze murder as a barrier to inheritance in terms of four schools of thought. This type of research is a literature study, namely by tracing many books and other scientific works which explain the opinion of the madhab imam regarding murder as a barrier to inheritance. All the found data were analyzed descriptively using the ijtihad approach of each madhhab priest. The results of the study explain that the opinion of Imam Shafi'i regarding murder as a barrier to obtaining inheritance is more widely used by scholars. He thinks that all types of murder, qotlu al-'amd (intentional), qotlu syibhu al-'amd (resembling intentional), qotlu al-khotho' (wrong) and qotlu al-haq (true/legal) are obstacles in obtaining property. inheritance.